2008
DOI: 10.1016/j.crohns.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

IBD patients need in health quality of care ECCO consensus

Abstract: : Evidence-based medicine in QoHC is limited. It is concluded that optimizing QoHC by "information"; "education", "benchmarking" and "psychological analysis" helps the patient to understand the disease and comply with its therapy, increasing QoL, reducing depression and anxiety. Future aspects regarding more evidence-based science and optimization of QoHC in IBD throughout Europe have been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 78 publications
0
45
0
4
Order By: Relevance
“…Recently, some studies have been applying marketing research strategies to assess patient satisfaction [11][12][13][14][15][16][17]. Like the pursuit of customer loyalty to products and services in the market, patient satisfaction is studied to evaluate the intentions of patient behavior to monitor and predict the return to service or to look for other providers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have been applying marketing research strategies to assess patient satisfaction [11][12][13][14][15][16][17]. Like the pursuit of customer loyalty to products and services in the market, patient satisfaction is studied to evaluate the intentions of patient behavior to monitor and predict the return to service or to look for other providers.…”
Section: Introductionmentioning
confidence: 99%
“…Barlow et al reported that self-management interventions showed improved outcomes in relation to symptom reporting, psychological well-being, and healthcare resource use, but that education alone was less promising [13]. Optimizing quality of health care by improving information, increasing education and access to psychological analysis was reported as helping the patient understand the disease and to comply with its therapy, increasing quality of life, and reducing depression and anxiety [14]. A pre-post evaluation study that introduced a proactive IBD service found that the disease burden decreased, improving clinical outcomes [15].…”
Section: Introductionmentioning
confidence: 99%
“…This issue was addressed in a paper by the ECCO Quality of Health Care group, regarding optimization of quality of health care in IBD through one avenue of a consensus of simple guidelines for GP's [52] , and a booklet has been produced by the American Gastroenterology Association outlying IBD patient's self-management strategies through the use of "action plan tools" [53] . These documents however, were not found through the systematic review indicating the need for a broader exposure.…”
mentioning
confidence: 99%